Luteinizing hormone-based modified GnRH antagonist protocol in normal responders undergoing in vitro fertilization treatment: A multi-center randomized controlled trial - Liu, Shan; Lv, Yasu; Liu, Minghui; Han, Shuo; Liu, Xiaoqun; Zhao, Zhiming; Cui, Wei; Yang, Aijun; Li, Yuan (Frontiers in Endocrinology, 2022)
Objective To study the clinical efficacy and cost-effectiveness of a modified gonadotrophin-releasing hormone (GnRH) antagonist protocol based on luteinizing hormone (LH) levels through one complete assisted reproductive technology (ART) cycle in normal responders. Design Non-inferiority, multicenter randomized controlled trial. Setting University-based hospitals and an academic medical center. Patients A total of 372 patients fulfilled the inclusion criteria and were eligible to participate. Intervention(s) Participants were randomized at a 1:1 ratio and stimulated with the conventional flexible GnRH antagonist protocol (control group) or LH-based modified GnRH antagonist protocol (study group). Main Outcome Measures The primary outcome was the cumulative ongoing pregnancy rate per aspiration. The secondary outcomes were number of oocytes retrieved, number of good quality embryos, cumulative positive βhCG rate, cumulative clinical pregnancy rate, pregnancy loss rate, moderate and severe ovarian hyperstimulation syndrome (OHSS), and financial expenditure. Results The cumulative ongoing pregnancy rate was 65.1% in the study group and 70.1% in the control group (odds ratio, 0.79; 95% confidence interval, 0.50–1.26; P = 0.33). The multivariate regression analyses results showed that the number of retrieved oocytes was positively associated with the odds for a higher cumulative ongoing pregnancy rate (adjusted odds ratio, 1.11, 95% confidence interval, 1.06–1.17, P < 0.001). The treatment protocol, female age, and body mass index were not independent predictors. The incremental cost-effectiveness ratio for luteinizing hormone-based gonadotrophin releasing hormone antagonist protocol versus the conventional flexible gonadotrophin releasing hormone antagonist protocol was estimated at 3568.6 USD for each additional ongoing pregnancy. Conclusion The luteinizing hormone-based gonadotrophin releasing hormone antagonist protocol had clinical efficacy similar to the conventional flexible gonadotrophin releasing hormone antagonist protocol in normal responders undergoing in vitro fertilization treatment but was more cost-effective considering the cumulative ongoing pregnancy rate in the entire assisted reproductive technology cycle. Clinical Trial Registration www.chictr.org.cn, identifier: ChiCTR1800018077 URL of the registration site http://www.chictr.org.cn/edit.aspx?pid=27389&htm=4. Trial registration date 29 August 2018. Date of first patient enrollment 1 September 2018.